Likert vs PI‐RADS v2: a comparison of two radiological scoring systems for detection of clinically significant prostate cancer. (1st November 2019) - Khoo, Christopher C.; Eldred‐Evans, David; Peters, Max; Bertoncelli Tanaka, Mariana; Noureldin, Mohamed; Miah, Saiful; Shah, Taimur; Connor, Martin J.; Reddy, Deepika; Clark, Martin; Lakhani, Amish; Rockall, Andrea; et al.
Abstract : Objective: To compare the clinical validity and utility of Likert assessment and the Prostate Imaging Reporting and Data System (PI‐RADS) v2 in the detection of clinically significant and insignificant prostate cancer. Patients and Methods: A total of 489 pre‐biopsy multiparametric magnetic resonance imaging (mpMRI) scans in consecutive patients were subject to prospective paired reporting using both Likert and PI‐RADS v2 by expert uro‐radiologists. Patients were offered biopsy for any Likert or PI‐RADS score ≥4 or a score of 3 with PSA density ≥0.12 ng/mL/mL. Utility was evaluated in terms of proportion biopsied, and proportion of clinically significant and insignificant cancer detected (both overall and on a 'per score' basis). In those patients biopsied, the overall accuracy of each system was assessed by calculating total and partial area under the receiver‐operating characteristic (ROC) curves. The primary threshold of significance was Gleason ≥3 + 4. Secondary thresholds of Gleason ≥4 + 3, Ahmed/UCL1 (Gleason ≥4 + 3 or maximum cancer core length [CCL] ≥6 or total CCL≥6) and Ahmed/UCL2 (Gleason ≥3 + 4 or maximum CCL ≥4 or total CCL ≥6) were also used. Results: The median (interquartile range [IQR]) age was 66 (60–72) years and the median (IQR) prostate‐specific antigen level was 7 (5–10) ng/mL. A similar proportion of men met the biopsy threshold and underwent biopsy in both groups (83.8% [Likert] vs 84.8% [PI‐RADS v2]; P = 0.704). The Likert system predicted more clinically significant cancers than PI‐RADS across all disease thresholds. Rates of insignificant cancers were comparable in each group. ROC analysis of biopsied patients showed that, although both scoring systems performed well as predictors of significant cancer, Likert scoring was superior to PI‐RADS v2, exhibiting higher total and partial areas under the ROC curve. Conclusions: Both scoring systems demonstrated good diagnostic performance, with similar rates of decision to biopsy. Overall, Likert was superior by all definitions of clinically significant prostate cancer. It has the advantages of being flexible, intuitive and allowing inclusion of clinical data. However, its use should only be considered once radiologists have developed sufficient experience in reporting prostate mpMRI.